Do Positivity and Sensitivity to Cyber-Bullying Decrease Cyber-Bullying? - Peker Adem; Kasikci Furkan (Sciendo, 2022)
Introduction: The use of social media tools is increasing day by day. In addition to its positive use, social media tools are also used in the virtual environment to harm others. This harmful use is noted as cyber-bullying. Determining the factors affecting cyber-bullying is of great importance in terms of contributing to intervention studies. This study aims to examine the moderate role of positivity and sensitivity towards cyber-bullying between cyber-victimization and cyber-bullying.